Discharge and densification in the spark plasma sintering of quasicrystal particles - Li, Ruitao (2021)
To investigate the micromechanisms involved in the spark plasma sintering of quasicrystals, thin foils were extracted from samples by focused ion beam at the interrupted states and analysed by transmission electron microscopy for the first time. Material jets are present between adjacent particles, indicating the occurrence of discharge/plasma. Surficial material melts first due to discharge and the liquid sputters as a result of the action of electric field, forming material jets. Discharge occurs in all the cavities with the largest gap size of 60 nm. Gap size is a deciding factor for the formation of material jets: Thick jets are only formed in narrow gaps (< 20 nm), while very thin jets or even no jets are present in wide gaps (> 20 nm). A low voltage (< 0.016 V) is needed to trigger the discharge, and it is inferred that quantum tunnelling and thermal excitation promote the formation of discharge within nanopores at relatively high temperatures. Discharge contributes very little to the densification, while the plastic deformation, meditated by a unique type of defect—metadislocations, is the dominant mechanism for it. The phase transformation of icosahedral Al–Cu–Fe–Cr to its crystalline approximants is accompanied by the formation of planar faults.